Industrial training report: Medical Record Department, An-Nur Hasanah Specialist Hospital / Nurain Ramli - Ramli, Nurain (Bachelor of Information Science (Hons.) Records Management, 2015)
In this report, the student joined the company of Hospital Pakar An-nur Hasanah as a trainee student at Medical Record Department during six month training. The position and responsibilities that have been given by company during industrial training to managing records keep in the medical records department. I Hospital Pakar Annur Hasanah has provided a system called Icare system to easier Medical Records Department manages the patient's files with systematic and efficient. IA project for the improvement of the Medical Records Department was carried out with successfully. In this report provides a detailed explanation about the projects that have been carried out during practical training. The main objective industrial training is give knowledge theoretically and also technically. During twenty week undergo industry training student can accept various skills and experience. The experience and learned gained during five month of industrial training at An-Nur Specialist Hospital. The whole training period was very interesting, instructive and challenging. Through this training was able to gain new insights and more comprehensive understanding about the real industry working condition and practice. The five month placement also has provided the opportunities to develop and improve soft and functional skill.